Stress corrosion of an austenitic stainless steel expansion joint, a case study. (March 2019) - Gomes da Silva, M.J.; Fragoso, H.A.P.; Barrio, R.C.A.G.; Cardoso, J.L.
Abstract: The duct system is one of the structures that most need a series of conditions that require the system to have a certain flexibility of movement due to thermal stresses, changes in the direction of the duct system and the unevenness on the ground. Metal bellows are designed to provide flexibility to the system, however, to guarantee the proper properties in service one should consider the material used in the component manufacturing as well as the manufacturing process itself. This research aimed to study a case of failure due to the stress corrosion of an austenitic stainless steel expansion joint. For the assessment of the main factors that led to the failure of the expansion joint, some analyses were employed: microstructural characterization by optical microscopy and scanning electron microscopy (SEM); X-ray diffraction; solution annealing heat treatments and microhardness. The results showed that the cleaning conditions allowed pits and cavities to form on the inner surface of the bellows while the forming processes used in the bellows manufacturing of the expansion joints were responsible for providing the necessary metallurgical conditions for the nucleation and propagation of cracks from pits and cavities. From the results it was possible to enumerate a series of recommendations that take into account an adequate cleaning of the component as well as the appropriate thermal treatments to optimize the service life of the studied component. Highlights: Corrosion resistance of expansion joint bellows Stress corrosion cracking of stainless steel Nucleation of cracks due to metallurgical conditions